Budd-Chiari Syndrome as A Manifestation of Right Atrium Myxoma - F, Komoni; L, Rakovica; F, Sherifi; F, Hyseni; V, Vokshi; AB, Siddik; M, Rahman; E, Ahsan; E, Mohamed; A, Guy; et al. (Archives of Clinical and Medical Case Reports, 2021)
Budd-Chiari syndrome (BCS) is a rare condition marked by a number of symptoms due to hepatic venous obstruction. A 40-year-old female patient presented with abdominal pain, distension, and dyspnea. An abdominal ultrasonogram showed hepatomegaly, splenomegaly and ascites. A hypodense mass obstructed hepatic flow suggested thrombus formation in the hepatic and portal veins and suprahepatic part of the inferior vena cava on computed tomography. Transthoracic echocardiography was performed to assess thrombus extension to inferior vena cava and underlying pathological processes. It showed a mass lesion in the right atrium near intra atrial septum about 4 × 3 cm in diameter. The lesion manifested as an intracardiac thrombus extending from the inferior vena cava. After the successful surgical removal, the diagnosis of the mass was confirmed as atrial myxoma by histopathological examinations. We conclude that right atrial myxoma is a rare cause of Budd-Chiari syndrome.